Breeding superman : Nietzsche, race and eugenics in Edwardian and interwar Britain - Stone, Dan, 1971- (Studies in social and political thought ;, 2002)
"Before the First World War there existed an intellectual turmoil in Britain as great as any in Germany, France or Russia, as the debates over Nietzsche and eugenics in the context of early modernism reveal. With the rise of fascism after 1918, these debates became more ideologically driven, with science and vitalist philosophy being hailed in some quarters as saviours from bourgeois decadence, vituperated in others as heralding the onset of barbarism. Breeding Superman looks at several of the leading Nietzscheans and eugenicists, and challenges the long-cherished belief that British intellectuals were fundamentally uninterested in race. The result is a study of radical ideas which are conventionally written out of histories of the politics and culture of the period"--